2021
DOI: 10.3389/fcimb.2021.653843
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Excretory-Secretory Products of Trichinella spiralis Adult Worms on Sepsis-Induced Acute Lung Injury in a Mouse Model

Abstract: Acute lung injury (ALI) is a common complication of systemic inflammation or sepsis with high morbidity and mortality. Although many studies have confirmed that helminth-derived proteins had strong immunomodulatory functions and could be used to treat inflammatory diseases, there is no report on the therapeutic effect of excretory-secretory products of Trichinella spiralis adult worms (Ts-AES) on sepsis-induced ALI. In this study, the therapeutic efficacy of Ts-AES on sepsis-induced ALI and the underlying immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…Intervention strategies (Tables 3 and 4), such as human recombinant cytokines (IL-15 and IL-36) (59,101), blocking phenotypes or chemokines [neuropilin (Nrp)-1, CTLA-4, lymphocyte activation gene (LAG)-3, and chemokine (C-X-C motif) ligand (CXCL) 4)] (50,58,77,82), nutrients (glutamine) (107), inhibiting molecules [sema3A, tissuenonspecific alkaline phosphatase (TNAP), Sirtuin1, P2Y12, COX-2, and poly ADP-ribose polymerase (PARP)] (48,51,102,(111)(112)(113), as well as even clinical therapeutics (high-volume hemofiltration, immunoglobulin, fresh frozen plasma, stem cells, and ulinastatin) (41,114,115,117,118) and traditional Chinese medicine (TCM) (electroacupuncture and tanshinone IIA) (103,106), can increase the chance of survival by inhibiting the heterogeneous characteristics of Treg-induced immunosuppression. Alternatively, other studies have shown improved outcomes in sepsis by increasing the heterogeneous characteristics of Tregs to inhibit sepsis-induced SIRS through intervention strategies such as human recombinant cytokines (IL-38 and IL-7) (96,97), blocking phenotypes or cytokines (CD28 and IL-3) (81,95), nutrients (arginine and fiber cellulose) (108,109), and others (bilirubin, ITK inhibitor, miR-126, maresin1, excretory-secretory products of Trichinella spiralis adult worms, and adipose-derived mesenchymal stem cell-derived exosomes) (19,20,70,98,99,116), as well as even clinical therapeutics (enteral nutrition and pre-and post-dilution during continuous veno-venous hemofiltration) (22,…”
Section: Treg Heterogeneity In Sepsismentioning
confidence: 99%
See 3 more Smart Citations
“…Intervention strategies (Tables 3 and 4), such as human recombinant cytokines (IL-15 and IL-36) (59,101), blocking phenotypes or chemokines [neuropilin (Nrp)-1, CTLA-4, lymphocyte activation gene (LAG)-3, and chemokine (C-X-C motif) ligand (CXCL) 4)] (50,58,77,82), nutrients (glutamine) (107), inhibiting molecules [sema3A, tissuenonspecific alkaline phosphatase (TNAP), Sirtuin1, P2Y12, COX-2, and poly ADP-ribose polymerase (PARP)] (48,51,102,(111)(112)(113), as well as even clinical therapeutics (high-volume hemofiltration, immunoglobulin, fresh frozen plasma, stem cells, and ulinastatin) (41,114,115,117,118) and traditional Chinese medicine (TCM) (electroacupuncture and tanshinone IIA) (103,106), can increase the chance of survival by inhibiting the heterogeneous characteristics of Treg-induced immunosuppression. Alternatively, other studies have shown improved outcomes in sepsis by increasing the heterogeneous characteristics of Tregs to inhibit sepsis-induced SIRS through intervention strategies such as human recombinant cytokines (IL-38 and IL-7) (96,97), blocking phenotypes or cytokines (CD28 and IL-3) (81,95), nutrients (arginine and fiber cellulose) (108,109), and others (bilirubin, ITK inhibitor, miR-126, maresin1, excretory-secretory products of Trichinella spiralis adult worms, and adipose-derived mesenchymal stem cell-derived exosomes) (19,20,70,98,99,116), as well as even clinical therapeutics (enteral nutrition and pre-and post-dilution during continuous veno-venous hemofiltration) (22,…”
Section: Treg Heterogeneity In Sepsismentioning
confidence: 99%
“…In addition to the role Tregs play in maintaining immune homeostasis in dedicated lymphoid tissues, these cells exist in other tissues such as the lung, liver, renal, muscle, brain and myocardium (73,87,98,99,102,148). Many tissue-specific Treg functions go beyond our initial understanding of Tregs as immune inflammation-specific inhibitors (70,99,133).…”
Section: Tissue-specific Treg Patterns In Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…is to maintain homeostasis ( 12 , 35 , 115 ). Many of these tissue-specific T regs functions, go beyond our initial understanding of T regs as immuno-inflammation-specific inhibitors ( 84 , 86 ), whereas a large number of previous intervention and observational studies on sepsis have focused on the functions and characteristics of T regs in the peripheral circulation and spleen ( 51 53 , 75 , 77 ). The timing and location of tissue-specific T regs -mediated immune homeostasis and regulation, remain undefined.…”
Section: T Regs -Related Therapeutic Potential In Saementioning
confidence: 99%